2007
DOI: 10.1016/j.entcs.2006.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Random Continuous Functions

Abstract: Electronic Notes in Theoretical Computer Science 167 (2007) 275-287. doi:10.1016/j.entcs.2006.08.016Received by publisher: 0000-01-01Harvest Date: 2016-01-04 12:23:44DOI: 10.1016/j.entcs.2006.08.016Page Range: 275-28

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…That is, one conceives of constructing a 'random' tree T with no dead ends by starting with the empty string and then, for each node σ ∈ T , including either one or both of the immediate successors σ i of σ with equal probability 1 3 . Brodhead, Cenzer and Dashti [6] defined a closed set Q ⊆ 2 N to be (Martin-Löf) random if x Q is (Martin-Löf) random. Note that the equal probability of 1 3 for the three cases of branching allows the application of Schnorr's theorem that Martin-Löf randomness is equivalent to prefix-free Kolmogorov randomness.…”
Section: S(abmentioning
confidence: 99%
See 2 more Smart Citations
“…That is, one conceives of constructing a 'random' tree T with no dead ends by starting with the empty string and then, for each node σ ∈ T , including either one or both of the immediate successors σ i of σ with equal probability 1 3 . Brodhead, Cenzer and Dashti [6] defined a closed set Q ⊆ 2 N to be (Martin-Löf) random if x Q is (Martin-Löf) random. Note that the equal probability of 1 3 for the three cases of branching allows the application of Schnorr's theorem that Martin-Löf randomness is equivalent to prefix-free Kolmogorov randomness.…”
Section: S(abmentioning
confidence: 99%
“…In [6], the notion of randomness was extended to continuous functions on 2 N . Thus, it will be natural to consider K-trivial continuous functions.…”
Section: K-trivial Continuous Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown in particular that every K-trivial class contains a K-trivial member, but there exist K-trivial Å 0 1 classes with no computable members. The related notion of a random continuous function was introduced in [3]. It was shown that a random continuous function F on 2 N cannot be computable, so that the graph of F cannot be Å 0 1 class.…”
Section: Conclusion and Future Researchmentioning
confidence: 99%
“…In a series of recent papers [2,3,4,5], G. Barmpalias, S. Dashti, R. Weber and the authors have defined a notion of (algorithmic) randomness for closed sets and continuous functions on 2 N . Some definitions are needed.…”
Section: Introductionmentioning
confidence: 99%